2017
DOI: 10.3389/fpls.2017.00597
|View full text |Cite
|
Sign up to set email alerts
|

Titanium as a Beneficial Element for Crop Production

Abstract: Titanium (Ti) is considered a beneficial element for plant growth. Ti applied via roots or leaves at low concentrations has been documented to improve crop performance through stimulating the activity of certain enzymes, enhancing chlorophyll content and photosynthesis, promoting nutrient uptake, strengthening stress tolerance, and improving crop yield and quality. Commercial fertilizers containing Ti, such as Tytanit and Mg-Titanit, have been used as biostimulants for improving crop production; however, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
184
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(200 citation statements)
references
References 168 publications
(191 reference statements)
12
184
3
1
Order By: Relevance
“…Numerous reports confirmed that protein hydrolysates, such as auxins and gibberellins, have hormone-like effects, stimulating root and shoot growth. This, in turn, has a positive effect on crop productivity [11,53,54,100,[102][103][104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports confirmed that protein hydrolysates, such as auxins and gibberellins, have hormone-like effects, stimulating root and shoot growth. This, in turn, has a positive effect on crop productivity [11,53,54,100,[102][103][104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium through increasing rate of photosynthesis and uptake nutrients (by increasing root volume) involved in chlorophyll and photosynthesis led to increasing plant growth (Haghighi and Daneshmand, 2018). Lyu et al, (2017) proposed that Ti has a positive effect on plant growth and quality of crops. Plants can complete their life cycle without titanium; there is no reported Ti deficiency in plants; and mechanisms of Ti action are still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Plants can complete their life cycle without titanium; there is no reported Ti deficiency in plants; and mechanisms of Ti action are still uncertain. Ti, however, is not an essential nutrient for plant based on the criteria for essentiality (Lyu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, the use of biostimulants has been constantly increasing for sustainable agriculture, because these substances enhance nutrient use efficiency, reduce fertilizers consumption, stimulate plant development and growth (Kunicki et al, 2010; Calvo et al, 2014; Halpern et al, 2015; Le Mire et al, 2016), and counteract stress factors, eventually enhancing crop quality and yield (Ziosi et al, 2013; Van Oosten et al, 2017). The interest in this sector is evidenced by the significant increase of research papers focused on it and by its economical relevance.…”
Section: Introductionmentioning
confidence: 99%